1991
DOI: 10.1038/351477a0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitric oxide in the reflex relaxation of the stomach to accommodate food or fluid

Abstract: The fundus of the guinea-pig stomach actively dilates in response to low increases in intragastric pressure. This physiological response, now called adaptive relaxation, accommodates the intake of liquid or food. It is independent of external innervation, resistant to ganglion blockade, but reflex in origin. The nerves involved are neither adrenergic nor cholinergic in nature. Non-adrenergic, non-cholinergic (NANC) nerves have now been recognized in many parts of the gastrointestinal tract and have recently be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
308
1
7

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(340 citation statements)
references
References 12 publications
24
308
1
7
Order By: Relevance
“…It has been proposed that the rapid rate of generation of U NO at the gastric-esophageal junction will expose this region to a high local nitrosative stress witch may be involved in the high incidence of epithelial mutagenesis and cancer at this anatomical site [54,55]. On the other hand, beneficial effects include host defense against gut pathogens that have the capacity to survive in acidic medium [56] and regulation of gastric mucosal blood flow, increasing mucous thickness [57,58] and gastric motility [59]. Further considering that wine phenolics may compete for nitration and nitrosation reactions with other molecules during digestion avoiding the formation of toxic compounds (notably carcinogenic nitrosamines), the reduction of nitrite shown here may reveal health-promoting effects of red wine in connection with U NO bioactivity previously unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the rapid rate of generation of U NO at the gastric-esophageal junction will expose this region to a high local nitrosative stress witch may be involved in the high incidence of epithelial mutagenesis and cancer at this anatomical site [54,55]. On the other hand, beneficial effects include host defense against gut pathogens that have the capacity to survive in acidic medium [56] and regulation of gastric mucosal blood flow, increasing mucous thickness [57,58] and gastric motility [59]. Further considering that wine phenolics may compete for nitration and nitrosation reactions with other molecules during digestion avoiding the formation of toxic compounds (notably carcinogenic nitrosamines), the reduction of nitrite shown here may reveal health-promoting effects of red wine in connection with U NO bioactivity previously unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…NG-nitro L-arginine (L-NOARG) and its methyl ester (L-NAME) were subsequently shown to be more potent inhibitors of NANC relaxation than L-NMMA in the anococcygeus of the rat and mouse, and could abolish relaxation Liu et al, 1991). Following these earlier studies, inhibitors of nitric oxide synthase were shown to inhibit certain forms of NANC inhibitory transmission in the gut (Bult et al, 1990;Dalziel et al, 1991;Desai et al, 1991), respiratory tract (Tucker et al, 1990;Li & Rand, 1991), reproductive system (Ignarro et al, 1990;Liu et al, 1991) and cerebral (Toda & Okamura, 1990) and penile arteries (Liu et al, 1991). Nitric oxide synthase has recently been identified in homogenates of BRP and rat anococcygeus muscle Sheng et al, 1991;1992) and consists of two fractions; a soluble form similar to that isolated from brain Schmidt et al, 1991) and a particulate form, both of which are activated by calcium, and like NANC relaxation, are blocked by L-NOARG.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibition was partially reversed after washout of L-NAME and incubation with L-arginine (L-Arg, 2 mM, 30 min; Figure 4) (control, 46.4 ± 1.4%; + L-NAME, 5.7 ± 1.0%; + L-Arg, 36.8 ± 3.5%; n = 4, P <0.001). Washout of L-NAME with L-Arg was attempted since coincubation of L-NAME (100 xM) with L-Arg (0.5-2 mM) does not reverse the inhibitory effect of L-NAME (Desai et al, 1991a), which could be because L-NAME is an irreversible inhibitor of NOS (Dwyer et al, 1991). Figure 2 A wholemount preparation of the myenteric plexus of the guinea pig stomach fundus immunostained for nitric oxide synthase (NOS) using the indirect immunofluorescence method.…”
Section: Tetrodotoxin Prevents Vagus-but Not Vip-induced Gastric Relamentioning
confidence: 99%